Self-efficacy and job satisfaction of teachers in schools for students with disabilities - Žunić-Pavlović Vesna P.; Pavlović Miroslav V. (Specijalna Edukacija i Rehabilitacija, 2020)
Introduction. Self-efficacy significantly affects teaching outcomes and professional life of teachers. Although there are numerous research studies on self-efficacy and job satisfaction of teachers, studies that deal with teachers in special education are scarce. Objectives. The research had the following two goals: first, to determine the differences in self-efficacy and job satisfaction between teachers in secondary schools for students with disabilities and teachers in secondary vocational schools, and second, to examine the relationship between self-efficacy and job satisfaction in these two groups of teachers. Methods. The sample consisted of 96 teachers in schools for students with disabilities and 372 teachers in vocational schools. Ohio State Teacher Efficacy Scale, Short form (OSTES) and Teaching Satisfaction Scale (TSS) were used. Results. Teachers in schools for students with disabilities differed significantly in the level of self-efficacy and job satisfaction compared to teachers in vocational schools. In both groups of teachers, there was a significant positive relation between self-efficacy and job satisfaction. Conclusion. The results of this research suggest that teachers with a higher level of self-efficiency are generally more satisfied with their job. This finding may have significant implications for teacher professional development. The determined differences between the two groups of teachers justify the need for an in-depth study of the relation between self-efficiacy and job satisfaction.